TRANSNASAL ENDOSOCPIC REPAIR OF CEREBROSPINAL FLUID RHINORRHOEA - Bhatti, Sajid Nazir; Khan, Shahbaz Ali; Shah, Rizwan; Aurangzeb, Ahsan; Ahmed, Ehtisham; Rizvi, Farhat; Zadran, Khalid Khan; Alvi, Nazir (Journal of Ayub Medical College Abbottabad, 2011)
Background: Cerebrospinal fluid (CSF) leaks can arise as a complication of trauma, hydrocephalus, endoscopic sinus surgery or it may occur spontaneously without any identifiable cause. Surgical repair is recommended in patients who do not respond to the conservative management. In recent years transnasal endoscopic approach has become the preferred method for repairing the CSF leaks and better outcomes have been reported as compared to the intracranial approaches that were previously used. Objective of this study was to analyse the outcome of transnasal endoscopic repair of CSF rhinorrhoea. Methods: This prospective study was conducted in the Department of Neurosurgery, Ayub Medical College, Abbottabad, from March 2007 to March 2010. Twenty-one patients with CSF rhinorrhoea were included in study that were diagnosed on the basis of clinical evaluation, glucose concentration of nasal discharge, computed tomography (CT) and magnetic resonance imaging (MRI). These patients did not respond to conservative management and were operated transnasally using rigid endoscope. Patients were followed up for a mean duration of 9 months and the outcome was analysed. Results: The patients included in the study ranged in the age group of 12-55 years. Among the patients 13 (57%) were female and 8 (38%) were males. The cause of CSF rhinorrhoea was traumatic in 16 (76.19%), Idiopathic or spontaneous in 4 (19.04%) and 1 (4.7%) case was related to endoscopic surgery for pituitary macroedenoma. In 10 (47.6.8%) patients the site of leak was cribriform plate, 5 (23.8%) had from sphenoid, 4 (19.04%) from frontal sinus and in 2 (9.5%) Ethmoid was affected. Primary surgery was successful in 17 (80.95%) of cases. In 2 (9.5%) cases re-exploration had to be performed. In 1 patient re-exploration had to be done for the third time. Overall success rate was 95%. One patient presented with CSF leak and meningitis 1 month after surgery and unfortunately died. Conclusion: Transnasal endoscopic repair of CSF rhinorrhoea is highly successful, safe and less traumatic. Keywords: Transnasal endoscopic repair, CSF Rhinorrhoea, CSF leak, transnasal endoscopic duroplasty